Pengelolaan Tenaga Kependidikan dalam Manajemen Penjaminan Mutu Pendidikan yang Berkualitas di MTSN 1 Pangandaran - Deti Kurnia; Fauzan Dhiahulhaq; Neneng Nurmalasari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The aim of this research is to reveal the management of educational personnel in quality assurance management through planning the needs of educational personnel at MtsN 1 Pangandaran. Educational personnel can be said to be one of the keys to the success or failure of providing education, so it is necessary to understand how to manage educational personnel and the aspects of managing educational personnel. Management can be defined as organizing or managing something so that the thing being managed can run smoothly in accordance with predetermined achievements, effectively and efficiently. The method used in this research is descriptive qualitative, namely presenting data described using words. The results of the research found that quality education staff in terms of how the teacher recruitment mechanism is carried out, carry out activities that can develop educators' performance abilities which are considered more effective because they increase the teaching staff's self-awareness regarding student discipline and build good relationships between students and teachers.